Musik Gamelan Drama Tradisional Amaq Abir - Silvia Yolanda As; Hary Murcahyanto; M Ridwan Markarma; Yuspianal Imtihan (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2021)
ABSTRACT This study aims to describe the composition of the traditional Gamelan music drama Amaq Abir in Sanggar Pustaka Budaya Marong Village, Central Lombok. This study used descriptive qualitative method. The results showed that Amaq Abir's Gamelan music has a composition of three types of Gending, namely: First Asmarandane Gending has a tempo between slow and fast with an expressive style with flat or horizontal melody and up to adjust the movements of the players on the stage. Both Oncer Prabu Gending have slow to medium tempo, dynamic a bit hard and a bit soft with a more even melody motion, up and down according to the scene. The three Gending Batelan has a fast tempo, getting louder and louder, the music style is light and fast with a rising melody motion, irregular tone movements. Each Gending has a rhythm that changes according to the situations and conditions of the play in the drama. The conclusion of the research is that the traditional Gamelan music of Amaq Abir has musical elements such as: rhythm, melody, harmony, tempo, dynamics, and style and is played with three types of gending with the Perembak technique and Bekilitan technique. Keywords: Gamelan Amaq Abir, Music Composition, Traditional Music